STOCK DIVIDENDS FROM THE VIEW-POINT OF THE DECLARING CORPORATION. - York, Thomas (The Accounting Review, 1941)
The article describes stock dividends from the viewpoint of the declaring corporations. The article focuses on three types of stock dividends namely, common on common, preferred on common and common or preferred on preferred. The first of these types of stock dividends, common on common, is of course, the one most frequently met with. It consists of the issue, gratis and ratably, of additional common shares to the common stockholders. Preferred shares issued to common stockholders, constitutes in effect a division or split-up of the total common stock interest into two parts, one of which is converted into, or reclassified as, a prior stock interest, and the other of which continues as the remaining common stock or residual interest. As the number of common shares is not affected by such stock dividend, each of these shares is the same fraction or aliquot part of the net corporate property as before the dividend. Another stock dividend is common or preferred stock issued to preferred stockholders. Strictly viewed, this type includes two sub-types.